The inhibitory effects of aureobasidin A on Candida planktonic and biofilm cells. Issue 2 (12th August 2012) - Tan, H. W.; Tay, S. T.
Summary Aureobasidin A (AbA) is a cyclic depsipeptide antifungal compound that inhibits a wide range of pathogenic fungi. In this study, the in vitro susceptibility of 92 clinical isolates of various Candida species against AbA was assessed by determining the planktonic and biofilm MICs of the isolates. The MIC50 and MIC90 of the planktonic Candida yeast were 1 and 1 μg ml−1, respectively, whereas the biofilm MIC50 and MIC90 of the isolates were 8 and ≥64 μg ml−1 respectively. This study demonstrates AbA inhibition on filamentation and biofilm development of C. albicans. The production of short hyphae and a lack of filamentation might have impaired biofilm development of AbA‐treated cells. The AbA resistance of mature Candidia biofilms (24 h adherent population) was demonstrated in this study.